STRATEGI PENANGANAN KENDALA DISTRIBUSI LOGISTIK PEMILU DI INDONESIA: TINJAUAN DARI PEMILU 2019 - Ananda Nabilla Putri; Saiza Syafira Elvandari; Azzahra Salsabila Hidayat; Putrie Saridewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The 2019 General Election in Indonesia was one of the largest democratic events in the world, involving complex logistical scales and diverse distribution challenges. This article aims to analyze strategies for addressing logistical distribution obstacles in the 2019 election, focusing on geographical factors, infrastructure, human resources, as well as planning and supervision. The study employs a descriptive qualitative approach, utilizing secondary data from official reports of the General Election Commission (KPU), academic studies, and media publications. The findings reveal that the main challenges in election logistics distribution in Indonesia include limited access to remote areas, extreme weather conditions, and a lack of inter-agency coordination. Strategies implemented include optimizing information technology for logistics tracking, collaboration with security forces, and enhanced training and simulations for logistics personnel. However, weaknesses in post-election evaluation hinder improvements in the distribution system for future elections. This article recommends the development of infrastructure in remote areas, increased transparency in the distribution process, and the implementation of technology-based monitoring systems to improve the quality of election administration. This study is expected to serve as a reference for policymakers in designing more effective and efficient logistical distribution strategies for future elections.